Marketing trends and strategies in nutrition and health - Kuliková, Sofia (2024)
This thesis explores the impact of marketing strategies on consumer behaviors in the nutrition and health sector. Through a detailed analysis of existing case studies, it identifies successful tactics, patterns, and potential drawbacks in marketing campaigns. The aim of the study is to optimise strategies to increase consumer engagement and provide practical recommendations to bridge the gap between theory and practice.